3D Hierarchical Composites of Hydrotalcite-Coated Carbon Microspheres as Catalysts in Baeyer–Villiger Oxidation Reactions - Marta Estrada-Ruiz; Daniel Cosano; Dolores Esquivel; Francisco J. Romero-Salguero; José Rafael Ruiz (Crystals, 2024)
The use of heterogeneous catalysts is fundamental in the search for sustainable chemical processes. Research on hierarchical materials is a growing field aimed at optimizing the synthesis of catalysts. In this work, layered materials with metals of different cationic ratios and three-dimensional hierarchical structures have been synthesized in a simple and easy way using carbon spheres as support. All materials were characterized with various techniques such as XRF, elemental analysis XRD, FT-IR, SEM, and TEM to study their composition and structure. Finally, these materials were used in the Baeyer–Villiger reaction, which was carried out under optimized conditions. The results showed that the metal ratio was an important factor in the coating process, affecting the catalytic capacity of the materials.